Transparency about net neutrality: A translation of the new European rules into a multi-stakeholder model - Pieter Nooren; Mark Prins (International Telecommunications Society (ITS), 2011)
The new European framework directive contains a number of policy objectives in the area of net neutrality. In support of these objectives, the universal service directive includes a transparency obligation for ISPs. This paper proposes a multi-stakeholder model for the implementation of this transparency obligation. The model is a multi-stakeholder model in the sense that it treats the content and form of the transparent information in close connection with the parties involved in the provision of the information and the processes in which they take part. Another crucial property of the model is that it distinguishes between technical and user-friendly information. This distinction makes it possible to limit the obligation to ISPs to the information for which they are in the best position to provide: the technical information on the traffic management measures that they apply, e.g., which traffic streams are subject to special treatment? Which measures are applied and when? The public availability of this technical information creates the opportunity for the other parties in the model to step in and contribute to the formulation of the user-friendly information for end users: which applications and services receive special treatment? When is their effect noticeable? It is expected that the involvement of other parties will lead to multiple, complementary routes for the formulation of the user-friendly information. Thus, the user-friendly information emerges in ways driven by market players and stakeholders that would be difficult to design and lay down in advance in the transparency obligation.
Keywords: L15; L96; L98; O38; 330; net neutrality; transparency; traffic management